Is the hemispheric asymmetry of sunspot cycle caused by an irregular process with long-term memory? - Das, Ratul; Ghosh, Aparup; Karak, Bidya Binay (Oxford University Press, 2022)
The hemispheric asymmetry of the sunspot cycle is a real feature of the Sun. However, its origin is still not well understood. Here, we perform nonlinear time series analysis of the sunspot area and number asymmetry to explore its dynamics. By measuring the correlation dimension of the sunspot asymmetry, we conclude that there is no strange attractor in the data. Further computing Higuchi’s dimension, we conclude that the hemispheric asymmetry is largely governed by stochastic noise. However, the behaviour of Hurst exponent reveals that the time series is not completely determined by a memory-less stochastic noise, rather there is a long-term persistence, which can go beyond two solar cycles. Therefore, our study suggests that the hemispheric asymmetry of the sunspot cycle is predominantly originated due to some irregular process in the solar dynamo. The long-term persistence in the solar cycle asymmetry suggests that the solar magnetic field has some memory in the convection zone.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: chaos; dynamo; methods; data analysis; Sun; activity; sunspots; Interactive devices; Solar energy; Time series analysis; Hemi-spheric asymmetries; Long term memory; Methods. Data analysis; Nonlinear time-series analysis; Stochastic noise